Mirror
The mirror design addresses the fragility of glass mirrors by incorporating chamfered edges and an anti-fog layer, resulting in improved durability and safety against impact.
Patent Information
- Application Number
- JP2024218189
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-07-11
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2040-07-10
AI Technical Summary
Mirrors made of glass plates are prone to chipping or breaking when dropped, due to their fragile nature.
A mirror design featuring a polygonal mirror body with chamfered portions on its edges and an anti-fog layer that covers at least a portion of the main surface, providing enhanced durability and impact resistance.
The mirror body's chamfered edges reduce the likelihood of chipping upon impact, while the anti-fog layer absorbs impact and prevents glass fragments from scattering, enhancing safety and durability.
Smart Images

Figure 2025039571000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a mirror. [Background technology]
[0002] There are various types of mirrors. For example, Patent Document 1 discloses an anticorrosive mirror. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2010-330 A Summary of the Invention [Problem to be solved by the invention]
[0004] Since mirrors are made of glass plates, they must be handled with care and may break or chip if dropped. The present invention has been made to solve the above problems, and aims to provide a mirror that is less likely to chip even if dropped. [Means for solving the problem]
[0005] Item 1. A mirror body is provided, which is formed in a polygonal shape in a plan view and has a first main surface on which an image is reflected, a second main surface opposite to the first main surface, and a peripheral surface connecting the first main surface and the second main surface; The peripheral surface includes a plurality of first end faces and second end faces connecting adjacent first end faces, A mirror, wherein the second end surface constitutes a first chamfered portion formed on the outer edge of the mirror body in a plan view.
[0006] Item 2. The mirror according to item 1, wherein a second chamfer is formed between the first main surface and the peripheral surface.
[0007] Item 3. The mirror according to item 1 or 2, further comprising an anti-fogging layer covering at least a portion of the first main surface.
[0008] Item 4. The mirror according to item 3, wherein the anti-fogging layer and the first main surface are chemically bonded to each other.
[0009] Item 5. The mirror according to item 3 or 4, further comprising an undercoat layer disposed between the antifogging layer and the first main surface.
[0010] Item 6. A second chamfered portion is formed between the first main surface and the peripheral surface, Item 6. The mirror according to any one of items 3 to 5, wherein the anti-fogging layer is arranged to cover the second chamfered portion.
[0011] Item 7. The mirror according to item 6, wherein the anti-fogging layer is disposed so as to cover the peripheral surface.
[0012] Item 8. The mirror according to item 7, wherein the anti-fogging layer has a pencil hardness of H to 2H.
[0013] Item 9. The mirror according to any one of Items 3 to 8, wherein the antifogging layer has a thickness of 2 to 12 μm.
[0014] Item 10. A mirror according to any one of items 3 to 9, wherein the anti-fogging layer is not disposed in a peripheral region of a predetermined width extending from the periphery of the first main surface toward the center.
[0015] Item 11. The mirror according to any one of Items 3 to 9, wherein the entire first main surface is covered with the anti-fogging layer.
[0016] Item 12. The anti-fogging layer is disposed so as to cover the peripheral surface, Item 12. The mirror according to any one of items 3 to 11, wherein the thickness of the anti-fogging layer disposed on the peripheral surface is greater than the thickness of the anti-fogging layer disposed on the first main surface.
[0017] Item 13. The mirror according to any one of Items 3 to 12, wherein the anti-fogging layer has anti-fogging properties due to hydrophilicity.
[0018] Item 14. The mirror according to item 13, wherein the anti-fogging layer further has anti-fogging properties due to water absorption.
[0019] Item 15. The mirror according to item 11, wherein the anti-fogging layer is made of a material containing a water-absorbent resin as a main component.
[0020] Item 16. The mirror according to item 15, wherein the water-absorbing resin contains at least one of an epoxy resin and a polyvinyl acetal resin.
[0021] Item 17. The mirror according to any one of Items 3 to 16, wherein the anti-fogging layer has a shatterproof function.
[0022] Item 18. The anti-fog mirror according to claim 17, wherein the anti-fog layer has a cross-linked structure formed by a hydrolyzable metal compound.
[0023] Item 19. The anti-fog mirror according to item 18, wherein the hydrolyzable metal compound is made of silicon alkoxide.
[0024] Item 20. The anti-fog mirror according to any one of Items 17 to 19, wherein the adhesion of the anti-fog layer to the mirror body is classified as 0 or 1 in a cross-cut test specified in JIS K5600-5-6.
[0025] Item 21. An anti-fog mirror described in any one of Items 17 to 20, in which a linear cut is formed on the second main surface of the mirror body with a cutter, a round rod placed on a horizontal plane is brought into contact with the anti-fog layer facing downward to correspond to the cut, and pressure is applied to both sides of the cut to split the mirror body, so that the anti-fog layer is not cut.
[0026] Item 22. A mirror according to any one of items 3 to 21, further comprising a protective film covering the anti-fogging layer.
[0027] Item 23. The protective film has a sheet-like substrate and an adhesive layer disposed on one surface of the substrate, The adhesive layer adheres the substrate to the anti-fogging layer, Item 23. The mirror according to item 22, wherein the peripheral portion of the substrate has an area where the adhesive layer is not disposed.
[0028] Item 24. The anti-fogging layer is disposed so as to cover the peripheral surface, Item 24. The mirror according to item 23, wherein the protective film is not adhered to at least a portion of the anti-fogging layer covering the peripheral surface.
[0029] Item 25. A mirror according to any one of items 22 to 24, wherein the protective film is formed so as to protrude from the mirror body at the location where the first chamfered portion is formed.
[0030] Item 26. The mirror according to any one of items 22 to 25, wherein the protective film has a bending strength of 96 to 131 MPa.
[0031] Item 27. The mirror according to any one of items 22 to 26, wherein the protective film has a thickness of 30 to 90 μm.
[0032] Item 28. A mirror according to any one of items 22 to 27, wherein the protective film is configured to cover the anti-fogging layer in a multiple-part divided state.
[0033] Item 29. The mirror body, a semi-metal layer laminated on one surface of the glass sheet; a resin protective layer laminated on the semi-metal layer; an inorganic oxide layer made of an inorganic oxide laminated between the semi-metal layer and the protective layer; Item 29. The mirror according to any one of items 1 to 28, comprising:
[0034] Item 30. The mirror of claim 29, wherein the semimetal layer is primarily composed of Si or Ge.
[0035] Item 31. The mirror body, A glass plate and A metal layer laminated on one surface of the glass plate; a resin protective layer laminated on the metal layer; Item 29. The mirror according to any one of items 1 to 28, comprising:
[0036] Item 32. The other surface of the glass plate constitutes the first main surface, Item 32. The mirror according to item 31, wherein an anti-fogging layer is disposed so as to cover the first main surface.
[0037] Item 33. In the peripheral surface, Item 33. The mirror of item 31 or 32, further comprising a peripheral protective layer disposed to cover a first interface between the glass plate and the metal layer and a second interface between the metal layer and the protective layer.
[0038] Item 34. The other surface of the glass plate constitutes the first main surface, An anti-fogging layer is disposed so as to cover the first main surface, In the peripheral surface, a peripheral protective layer disposed to cover a first interface between the glass sheet and the metal layer and a second interface between the metal layer and the protective layer; Item 32. The mirror according to item 31, wherein a portion of the anti-fogging layer covers the peripheral protective layer.
[0039] Item 35. The mirror according to item 33 or 34, wherein the peripheral protective layer is formed of an ultraviolet curable resin.
[0040] Item 36. A mirror according to any one of items 33 to 35, wherein an end face of the glass plate exposed to the outside at the peripheral surface has an area that is not covered with the peripheral protective layer.
[0041] Item 37. The mirror further includes a shatterproof film that prevents fragments from scattering when the mirror body is broken. Item 37. The mirror according to any one of items 31 to 36, wherein the shatterproof film is disposed so as to cover the protective layer.
[0042] Item 38. The mirror according to any one of items 31 to 37, wherein the protective layer has multiple types of information printed on it.
[0043] Item 39. The mirror according to any one of items 3 to 38, wherein the anti-fogging layer takes 30 seconds or more to form condensation. Effect of the Invention
[0044] According to the present invention, it is possible to make the device less susceptible to chipping even when dropped. [Brief description of the drawings]
[0045] [Figure 1] FIG. 1 is a plan view showing an embodiment of a mirror according to the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of FIG. [Diagram 3] FIG. 4 is a cross-sectional view showing another example of a mirror according to the present invention. [Figure 4] FIG. 4 is a cross-sectional view showing another example of a mirror according to the present invention. [Diagram 5] FIG. 4 is a cross-sectional view showing another example of a mirror according to the present invention. [Figure 6] FIG. 4 is a cross-sectional view showing another example of a mirror according to the present invention. [Figure 7] FIG. 2 is a schematic diagram of an apparatus for evaluating anti-fogging performance. [Figure 8] FIG. 4 is a cross-sectional view showing another example of a mirror according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0046] Hereinafter, an embodiment of a mirror according to the present invention will be described with reference to the drawings. The mirror according to this embodiment includes a mirror body. Below, the mirror body will be described first, and then various additional elements such as an anti-fogging layer that are added to the mirror body will be described. <1. Overview of the mirror body> Fig. 1 is a plan view of the mirror body, and Fig. 2 is a cross-sectional view of the mirror body taken along line AA. As shown in Fig. 1 and Fig. 2, the mirror body 1 has an outer shape formed in a rectangular shape when viewed from above, and has a first main surface 11 on which an image is reflected, a second main surface 12 opposite to the first main surface 11, and a peripheral surface 13 connecting the first main surface 11 and the second main surface 12. However, the planar shape of the mirror body 1 is not particularly limited, and it can be formed into a polygonal shape in addition to the rectangular shape shown in Fig. 1.
[0047] The peripheral surface 13 includes four first end faces 131 and second end faces 132 connecting adjacent first end faces 131 to each other. The four first end faces 131 are end faces constituting the four main sides of a rectangle, and adjacent first end faces 131 are perpendicular to each other. The second end faces 132 are connected to adjacent first end faces 131 so as to extend obliquely in a plan view. That is, the second end faces 132 form a chamfered portion of the peripheral edge of the mirror body 1 in a plan view. Hereinafter, the second end faces 132 may be referred to as a first chamfered portion.
[0048] 1 and 2, a chamfered portion 14 can be formed between the first main surface 11 and the peripheral surface 13, but is not essential. Hereinafter, this chamfered portion 14 may be referred to as a second chamfered portion. The second chamfered portion 14 is formed in the glass plate 2, which will be described later, in a cross section, and is connected to the first main surface 11 and the peripheral surface 13 so as to extend obliquely.
[0049] 2. Layer structure of the mirror body 2, the mirror body 1 has a glass plate 2 having a first surface (lower surface) and a second surface (upper surface), a metal layer 3 laminated on the first surface of the glass plate 2, and a protective layer 4 laminated so as to cover the metal layer 3, with the second surface of the glass plate 2 forming a first main surface 11. Below, each member constituting the mirror body 1 will be described.
[0050] <2-1. Glass plate> The glass plate 2 according to the present embodiment may be a known glass plate, and may be made of heat absorbing glass, general clear glass, green glass, or UV green glass. Examples of clear glass, heat absorbing glass, and soda lime glass are shown below.
[0051] (Clear glass) SiO2:70~73% by mass Al2O3:0.6~2.4% by mass CaO: 7~12% by mass MgO: 1.0~4.5% by mass RO: 13 to 15 mass% (R is an alkali metal) Total iron oxide converted to Fe2O3 (T-Fe2O3): 0.08-0.14 mass%
[0052] (Heat absorbing glass) The composition of the heat ray absorbing glass can be, for example, based on the composition of clear glass, with the ratio of total iron oxide converted to Fe2O3 (T-Fe2O3) being 0.4 to 1.3 mass%, the ratio of CeO2 being 0 to 2 mass%, the ratio of TiO2 being 0 to 0.5 mass%, and the glass skeletal components (mainly SiO2 and Al2O3) being reduced by the increases in T-Fe2O3, CeO2, and TiO2.
[0053] (Soda-lime glass) SiO2: 65~80% by mass Al2O3: 0~5% by mass CaO: 5~15% by mass MgO: 2% by mass or more NaO: 10~18% by mass K2O: 0~5% by mass MgO+CaO: 5~15% by mass Na2O+K2O: 10~20% by mass SO3:0.05~0.3% by mass B2O3:0~5% by mass Total iron oxide converted to Fe2O3 (T-Fe2O3): 0.02-0.03 mass%
[0054] The thickness of the glass plate 2 according to this embodiment is not particularly limited, but is preferably, for example, 1 to 10 mm, and more preferably 3 to 8 mm.
[0055] <2-2. Metal layer> The metal layer 3 is composed of a silver mirror film 31 and a copper film 32. That is, a known silver mirror film 31 that reflects an image is laminated on the first surface of the glass plate 2, and a copper film 32 is further laminated so as to cover this silver mirror film 31. The copper film 32 functions as a protective layer for the silver mirror film 31. However, it is also possible to omit the copper film 32 and form the metal layer only with the silver mirror film 31.
[0056] <2-3.Protective layer> Protective layer 4 is a layer that covers copper film 32, and can be made of a resin material such as epoxy resin, acrylic silicone resin, etc. In addition, various information related to the mirror, such as the manufacturing site and date of the mirror, and information on the anti-fogging layer described below, can be added to this protective layer 4 by printing or the like.
[0057] <2-4. Peripheral protection layer> Since the mirror body 1 is constructed by laminating the glass plate 2, the metal layer 3, and the protective layer 4 in this order, the interface between them is exposed on the peripheral surface 13. Therefore, if moisture penetrates from these interfaces, the metal layer 3 may deteriorate. Therefore, as necessary, as shown in FIG. 3, a peripheral protective layer 5 covering the peripheral surface 13 of the mirror body 1 can be provided. The peripheral protective layer 5 can be formed of a resin material, for example, a UV-curable resin, a two-liquid epoxy resin, a thermosetting resin, or the like. In addition, in order to make it easier to laminate the peripheral protective layer 5, as shown in FIG. 4, a diagonal cutout (which can also be a chamfered portion) can be formed in the cross section of the peripheral surface 13, and the peripheral protective layer 5 can be laminated so as to cover the cutout. In this case, as shown in FIG. 4, the end surface of the glass plate 2 may be exposed or may be covered with the peripheral protective layer 5. The notch is formed obliquely inward from the end face of the glass plate 2 toward the protective layer 4, and the interfaces between the glass plate 2, the metal layer 3, and the protective layer 4 are positioned in this notch.
[0058] <3. Anti-fogging layer> 5, an anti-fogging layer 7 can be laminated, if necessary, on the second main surface 12 of the glass plate 2 of the mirror body 1. The anti-fogging layer 7 will be described in detail below.
[0059] The anti-fogging layer 7 is not particularly limited as long as it has an anti-fogging effect on the glass plate 2, and a known anti-fogging layer can be used. Generally, the anti-fogging layer 7 is classified into a hydrophilic type that forms a water film on the surface from water generated from water vapor, a water-absorption type that absorbs water vapor, a water-repellent / water-absorption type that makes it difficult for water droplets to condense on the surface, and a water-repellent type that repels water droplets generated from water vapor, and any type of anti-fogging layer can be applied. As an example, an example of a water-repellent / water-absorption type anti-fogging layer will be described below. [Organic-inorganic composite anti-fog layer] The organic-inorganic composite anti-fogging layer is a single layer film or a laminated multi-layer film formed on the surface of the glass plate 2. The organic-inorganic composite anti-fogging layer contains at least a water-absorbing resin, a water-repellent group, and a metal oxide component. The anti-fogging layer 7 may further contain other functional components as necessary. Any type of water-absorbing resin may be used as long as it is a resin that can absorb and retain water. The water-repellent group can be supplied to the anti-fogging layer 7 from a metal compound having a water-repellent group (a water-repellent group-containing metal compound). The metal oxide component can be supplied to the anti-fogging layer 7 from a water-repellent group-containing metal compound or other metal compounds, metal oxide fine particles, etc. Each component will be described below.
[0060] (Water absorbent resin) The water-absorbent resin is not particularly limited, and examples thereof include polyethylene glycol, polyether resin, polyurethane resin, starch resin, cellulose resin, acrylic resin, epoxy resin, polyester polyol, hydroxyalkyl cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl acetal resin, polyvinyl acetate, etc. Among these, preferred are hydroxyalkyl cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl acetal resin, polyvinyl acetate, epoxy resin, and polyurethane resin, more preferred are polyvinyl acetal resin, epoxy resin, and polyurethane resin, and particularly preferred is polyvinyl acetal resin.
[0061] The polyvinyl acetal resin can be obtained by acetalizing polyvinyl alcohol by condensation reaction with aldehyde. The acetalization of polyvinyl alcohol may be carried out by a known method such as a precipitation method using an aqueous medium in the presence of an acid catalyst, or a dissolution method using a solvent such as alcohol. The acetalization can also be carried out in parallel with the saponification of polyvinyl acetate. The acetalization degree is preferably 2 to 40 mol%, more preferably 3 to 30 mol%, particularly preferably 5 to 20 mol%, and in some cases 5 to 15 mol%. The acetalization degree can be measured, for example, based on 13C nuclear magnetic resonance spectroscopy. The polyvinyl acetal resin having an acetalization degree in the above range is suitable for forming an organic-inorganic composite anti-fogging layer having good water absorption and water resistance.
[0062] The average polymerization degree of polyvinyl alcohol is preferably 200 to 4500, more preferably 500 to 4500. A high average polymerization degree is advantageous for the formation of an organic-inorganic composite anti-fogging layer having good water absorption and water resistance, but if the average polymerization degree is too high, the viscosity of the solution becomes too high, which may cause problems in the formation of the film. The saponification degree of polyvinyl alcohol is preferably 75 to 99.8 mol%.
[0063] Examples of the aldehyde to be condensed with polyvinyl alcohol include aliphatic aldehydes such as formaldehyde, acetaldehyde, butylaldehyde, hexylcarbaldehyde, octylcarbaldehyde, and decylcarbaldehyde. Examples of the aldehyde to be condensed with polyvinyl alcohol include benzaldehyde; 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, and other alkyl group-substituted benzaldehydes; chlorobenzaldehyde and other halogen atom-substituted benzaldehydes; substituted benzaldehydes in which hydrogen atoms are substituted with functional groups other than alkyl groups such as hydroxyl groups, alkoxy groups, amino groups, and cyano groups; and aromatic aldehydes such as condensed aromatic ring aldehydes such as naphthaldehyde and anthraldehyde. Aromatic aldehydes that are highly hydrophobic are advantageous in forming an organic-inorganic composite anti-fogging layer that has a low degree of acetalization and excellent water resistance. The use of an aromatic aldehyde is advantageous in that a film having high water absorption can be formed while leaving many hydroxyl groups. The polyvinyl acetal resin preferably contains an acetal structure derived from an aromatic aldehyde, particularly benzaldehyde.
[0064] Examples of epoxy resins include glycidyl ether epoxy resins, glycidyl ester epoxy resins, glycidyl amine epoxy resins, cyclic aliphatic epoxy resins, etc. Among these, cyclic aliphatic epoxy resins are preferred.
[0065] The polyurethane resin may be a polyurethane resin composed of a polyisocyanate and a polyol. As the polyol, an acrylic polyol and a polyoxyalkylene polyol are preferable.
[0066] The organic-inorganic composite anti-fogging layer contains a water-absorbing resin as a main component. In the present invention, the "main component" means the component with the highest content by mass. The content of the water-absorbing resin based on the weight of the organic-inorganic composite anti-fogging layer is preferably 50% by weight or more, more preferably 60% by weight or more, particularly preferably 65% by weight or more, and is 95% by weight or less, more preferably 90% by weight or less, from the viewpoints of film hardness, water absorbency, and anti-fogging properties.
[0067] (Water-repellent base) In order to fully obtain the above-mentioned effects of the water-repellent group, it is preferable to use a water-repellent group having high water repellency. The preferred water-repellent group is at least one selected from (1) linear or cyclic alkyl groups having 3 to 30 carbon atoms, and (2) linear or cyclic alkyl groups having 1 to 30 carbon atoms in which at least a portion of the hydrogen atoms has been substituted with fluorine atoms (hereinafter sometimes referred to as "fluorine-substituted alkyl groups").
[0068] Regarding (1) and (2), the chain or cyclic alkyl group is preferably a chain alkyl group. The chain alkyl group may be a branched alkyl group, but is preferably a linear alkyl group. An alkyl group having more than 30 carbon atoms may cause the antifogging layer 7 to become cloudy. From the viewpoint of the balance between the antifogging property, strength, and appearance of the film, the number of carbon atoms of the alkyl group is preferably 20 or less, more preferably 6 to 14. Particularly preferred alkyl groups are linear alkyl groups having 6 to 14 carbon atoms, particularly 6 to 12 carbon atoms, such as n-hexyl group (6 carbon atoms), n-decyl group (10 carbon atoms), and n-dodecyl group (12 carbon atoms). Regarding (2), the fluorine-substituted alkyl group may be a group in which only a part of the hydrogen atoms of a chain or cyclic alkyl group are substituted with fluorine atoms, or a group in which all of the hydrogen atoms of a chain or cyclic alkyl group are substituted with fluorine atoms, such as a linear perfluoroalkyl group. Since the fluorine-substituted alkyl group has high water repellency, a sufficient effect can be obtained by adding a small amount of it. However, if the content of the fluorine-substituted alkyl group is too high, it may separate from other components in the coating liquid for forming the film.
[0069] (Hydrolyzable metal compounds having water-repellent groups) In order to incorporate the water-repellent group into the anti-fogging layer 7, a metal compound having a water-repellent group (water-repellent group-containing metal compound), particularly a metal compound having a water-repellent group and a hydrolyzable functional group or a halogen atom (water-repellent group-containing hydrolyzable metal compound) or its hydrolysate may be added to the coating liquid for forming the film. In other words, the water-repellent group may be derived from a water-repellent group-containing hydrolyzable metal compound. As the water-repellent group-containing hydrolyzable metal compound, a water-repellent group-containing hydrolyzable silicon compound represented by the following formula (I) is suitable. RmSiY4-m (I) Here, R is a water-repellent group, that is, a linear or cyclic alkyl group having 1 to 30 carbon atoms in which at least a part of hydrogen atoms may be substituted with fluorine atoms, Y is a hydrolyzable functional group or a halogen atom, and m is an integer of 1 to 3. The hydrolyzable functional group is, for example, at least one selected from an alkoxyl group, an acetoxy group, an alkenyloxy group, and an amino group, and is preferably an alkoxy group, particularly an alkoxy group having 1 to 4 carbon atoms. The alkenyloxy group is, for example, an isopropenoxy group. The halogen atom is preferably chlorine. The functional groups exemplified here can also be used as the "hydrolyzable functional group" described below. m is preferably 1 to 2.
[0070] Upon completion of hydrolysis and polycondensation, the compound represented by formula (I) provides a component represented by the following formula (II): RmSiO(4-m) / 2 (II) where R and m are as defined above. After hydrolysis and polycondensation, the compound represented by formula (II) actually forms a network structure in the antifogging layer 7 in which silicon atoms are bonded to each other via oxygen atoms.
[0071] In this way, the compound represented by formula (I) is hydrolyzed or partially hydrolyzed, and further at least partially polycondensed to form a network structure of siloxane bonds (Si-O-Si) in which silicon atoms and oxygen atoms are alternately connected and spread three-dimensionally. The silicon atoms contained in this network structure are connected to water-repellent groups R. In other words, the water-repellent groups R are fixed to the network structure of siloxane bonds via bonds R-Si. This structure is advantageous in terms of uniformly dispersing the water-repellent groups R in the film. The network structure may contain a silica component provided by a silicon compound (e.g., tetraalkoxysilane, silane coupling agent) other than the water-repellent group-containing hydrolyzable silicon compound represented by formula (I). When a silicon compound (water-repellent group-free hydrolyzable silicon compound) having no water-repellent groups and a hydrolyzable functional group or halogen atom and a halogen atom is blended with the water-repellent group-containing hydrolyzable silicon compound in the coating liquid for forming the anti-fogging layer 7, a network structure of siloxane bonds including silicon atoms bonded to water-repellent groups and silicon atoms not bonded to water-repellent groups can be formed. With such a structure, it becomes easy to adjust the content of the water-repellent group and the content of the metal oxide component in the anti-fogging layer independently of each other.
[0072] The water-repellent group has the effect of improving the permeability of water vapor on the surface of the anti-fogging layer 7 containing the water-absorbing resin, thereby improving the anti-fogging performance. Since the two functions of water absorption and water repellency are mutually exclusive, water-absorbing materials and water-repellent materials have conventionally been provided in separate layers, but the water-repellent group eliminates uneven distribution of water near the surface of the anti-fogging layer, extends the time until condensation occurs, and improves the anti-fogging properties of the anti-fogging layer having a single layer structure. The effects of this will be explained below.
[0073] The water vapor that penetrates into the anti-fogging layer 7 containing the water-absorbing resin is hydrogen-bonded with the hydroxyl groups of the water-absorbing resin and is held in the form of bound water. As the amount of water-absorbing resin increases, the water vapor changes from the form of bound water to the form of semi-bound water, and finally becomes held in the form of free water held in the voids in the anti-fogging layer. In the anti-fogging layer 7, the water-repellent groups prevent the formation of hydrogen bonds and facilitate the dissociation of the formed hydrogen bonds. If the content of the water-absorbing resin is the same, there is no difference in the number of hydroxyl groups capable of hydrogen bonding in the film, but the water-repellent groups reduce the rate of formation of hydrogen bonds. Therefore, in the anti-fogging layer 7 containing the water-repellent groups, the water is ultimately held in the film in one of the above forms, but it can diffuse as water vapor to the bottom of the film before it is held. In addition, the water that is once held is also relatively easily dissociated and easily moves to the bottom of the film in the form of water vapor. As a result, the distribution of the amount of water held in the thickness direction of the film becomes relatively uniform from the vicinity of the surface to the bottom of the film. In other words, the entire thickness of the anti-fogging layer is effectively utilized to absorb water supplied to the film surface, so that water droplets are less likely to condense on the surface, and anti-fogging properties are enhanced. Furthermore, since water droplets are less likely to condense on the surface, the anti-fogging layer that has absorbed moisture has the characteristic of being less likely to freeze even at low temperatures.
[0074] On the other hand, in the anti-fogging layer that does not contain water repellent groups, the water vapor that penetrates into the film is very easily retained in the form of bound water, semi-bound water or free water. Therefore, the water vapor that penetrates tends to be retained near the surface of the film. As a result, the moisture in the film is extremely high near the surface and decreases rapidly as it progresses to the bottom of the film. In other words, although the bottom of the film can still absorb water, the moisture near the surface of the film is saturated with moisture and condenses as water droplets, resulting in limited anti-fogging properties.
[0075] When a water-repellent group is introduced into the anti-fogging layer using a hydrolyzable silicon compound containing a water-repellent group (see formula (I)), a strong network structure of siloxane bonds (Si-O-Si) is formed. The formation of this network structure is advantageous not only in terms of abrasion resistance but also in terms of improving hardness, water resistance, etc.
[0076] The water-repellent group is preferably added to such an extent that the contact angle of water on the surface of the anti-fogging layer is 70 degrees or more, preferably 80 degrees or more, more preferably 90 degrees or more. The water contact angle is measured by dropping 4 mg of water droplets on the surface of the film. In particular, when a methyl group or an ethyl group, which has a relatively weak water repellency, is used as the water-repellent group, it is preferable to incorporate the water-repellent group in the anti-fogging layer in an amount that makes the water contact angle in the above range. The upper limit of this water droplet contact angle is not particularly limited, but it is, for example, 150 degrees or less, for example, 120 degrees or less, or even 100 degrees or less. It is preferable that the water-repellent group is uniformly contained in the anti-fogging layer so that the contact angle of the water droplet is in the above range in all areas of the surface of the anti-fogging layer.
[0077] The anti-fogging layer preferably contains water-repellent groups in an amount within the range of 0.05 parts by mass or more, preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and 10 parts by mass or less, preferably 5 parts by mass or less, relative to 100 parts by mass of the water-absorbent resin.
[0078] (Inorganic oxides) The inorganic oxide is, for example, an oxide of at least one element selected from Si, Ti, Zr, Ta, Nb, Nd, La, Ce and Sn, and contains at least an oxide of Si (silica). The organic-inorganic composite anti-fogging layer preferably contains 0.01 parts by weight or more, more preferably 0.1 parts by weight or more, even more preferably 0.2 parts by weight or more, particularly preferably 1 part by weight or more, most preferably 5 parts by weight or more, in some cases 10 parts by weight or more, if necessary 20 parts by weight or more, and preferably 50 parts by weight or less, more preferably 45 parts by weight or less, even more preferably 40 parts by weight or less, particularly preferably 35 parts by weight or less, most preferably 33 parts by weight or less, in some cases 30 parts by weight or less, relative to 100 parts by weight of the water-absorbing resin. The inorganic oxide is a component necessary for ensuring the strength, particularly the abrasion resistance, of the organic-inorganic composite anti-fogging layer, but if the content of the inorganic oxide is high, the anti-fogging property of the organic-inorganic composite anti-fogging layer decreases.
[0079] (Inorganic oxide fine particles) The organic-inorganic composite anti-fogging layer may further contain inorganic oxide fine particles as at least a part of the inorganic oxide. The inorganic oxide constituting the inorganic oxide fine particles is, for example, an oxide of at least one element selected from Si, Ti, Zr, Ta, Nb, Nd, La, Ce and Sn, and is preferably silica fine particles. The silica fine particles can be introduced into the organic-inorganic composite anti-fogging layer by, for example, adding colloidal silica. The inorganic oxide fine particles are excellent in the function of transmitting the stress applied to the organic-inorganic composite anti-fogging layer to the article supporting the organic-inorganic composite anti-fogging layer, and also have high hardness. Therefore, the addition of inorganic oxide fine particles is advantageous from the viewpoint of improving the abrasion resistance of the organic-inorganic composite anti-fogging layer. In addition, when inorganic oxide fine particles are added to the organic-inorganic composite anti-fogging layer, fine voids are formed at the site where the fine particles are in contact or in close proximity, and water vapor is easily taken into the film through these voids. For this reason, the addition of inorganic oxide fine particles may be advantageous in improving the anti-fogging properties. The inorganic oxide fine particles can be provided to the organic-inorganic composite anti-fogging layer by adding preformed inorganic oxide fine particles to a coating liquid for forming the organic-inorganic composite anti-fogging layer.
[0080] If the average particle size of the inorganic oxide fine particles is too large, the organic-inorganic composite anti-fogging layer may become cloudy, and if it is too small, it may become difficult to disperse the inorganic oxide fine particles uniformly due to aggregation. From this viewpoint, the average particle size of the inorganic oxide fine particles is preferably 1 to 20 nm, more preferably 5 to 20 nm. Here, the average particle size of the inorganic oxide fine particles is described in the state of primary particles. The average particle size of the inorganic oxide fine particles is determined by measuring the particle sizes of 50 particles arbitrarily selected by observation using a scanning electron microscope and adopting the average value. If the content of the inorganic oxide fine particles is high, the water absorption amount of the organic-inorganic composite anti-fogging layer as a whole may decrease, and the organic-inorganic composite anti-fogging layer may become cloudy. The inorganic oxide fine particles are preferably added in an amount of 0 to 50 parts by weight, more preferably 2 to 30 parts by weight, further preferably 5 to 25 parts by weight, and particularly preferably 10 to 20 parts by weight, relative to 100 parts by weight of the water-absorbing resin.
[0081] (Hydrolyzable metal compounds without water-repellent groups) The anti-fogging layer may contain a metal oxide component derived from a hydrolyzable metal compound that does not have a water-repellent group (hydrolyzable compound that does not contain a water-repellent group). A preferred hydrolyzable metal compound that does not contain a water-repellent group is a hydrolyzable silicon compound that does not have a water-repellent group. The hydrolyzable silicon compound that does not have a water-repellent group is, for example, at least one silicon compound (not having a water-repellent group) selected from silicon alkoxide, chlorosilane, acetoxysilane, alkenyloxysilane, and aminosilane, and is preferably a silicon alkoxide that does not have a water-repellent group. An example of the alkenyloxysilane is isopropenoxysilane.
[0082] The hydrolyzable silicon compound having no water repellent group may be a compound represented by the following formula (III). SiY4 (III) As described above, Y is a hydrolyzable functional group, and is preferably at least one selected from an alkoxyl group, an acetoxy group, an alkenyloxy group, an amino group, and a halogen atom.
[0083] The hydrolyzable metal compound not containing a water-repellent group is hydrolyzed or partially hydrolyzed, and further, at least a part of the compound is polycondensed to provide a metal oxide component in which a metal atom is bonded to an oxygen atom. This component firmly bonds the metal oxide fine particles to the water-absorbent resin, and can contribute to improving the abrasion resistance, hardness, water resistance, etc. of the anti-fogging layer. The metal oxide component derived from the hydrolyzable metal compound not containing a water-repellent group is preferably in the range of 0 to 40 parts by mass, preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, particularly preferably 3 to 10 parts by mass, and in some cases 4 to 12 parts by mass, relative to 100 parts by mass of the water-absorbent resin.
[0084] A preferred example of a hydrolyzable silicon compound having no water-repellent group is a tetraalkoxysilane, more specifically, a tetraalkoxysilane having an alkoxy group having a carbon number of 1 to 4. The tetraalkoxysilane is, for example, at least one selected from tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, tetraisopropoxysilane, tetra-n-butoxysilane, tetraisobutoxysilane, tetra-sec-butoxysilane, and tetra-tert-butoxysilane.
[0085] If the content of the metal oxide (silica) component derived from tetraalkoxysilane is too high, the antifogging properties of the antifogging layer may decrease. One of the reasons is that the flexibility of the antifogging layer decreases, limiting the swelling and shrinkage of the film accompanying the absorption and release of moisture. The metal oxide component derived from tetraalkoxysilane is added in the range of 0 to 30 parts by mass, preferably 1 to 20 parts by mass, and more preferably 3 to 10 parts by mass, relative to 100 parts by mass of the water-absorbing resin.
[0086] Another preferred example of the hydrolyzable silicon compound without a water-repellent group is a silane coupling agent. The silane coupling agent is a silicon compound having reactive functional groups different from each other. The reactive functional group is preferably a part of a hydrolyzable functional group. The silane coupling agent is, for example, a silicon compound having an epoxy group and / or an amino group and a hydrolyzable functional group. Preferred silane coupling agents include glycidyloxyalkyltrialkoxysilane and aminoalkyltrialkoxysilane. In these silane coupling agents, the number of carbon atoms of the alkylene group directly bonded to the silicon atom is preferably 1 to 3. Since the glycidyloxyalkyl group and the aminoalkyl group contain a functional group (epoxy group, amino group) that shows hydrophilicity, they are not water-repellent as a whole, although they contain an alkylene group.
[0087] The silane coupling agent strongly bonds the water-absorbing resin, which is an organic component, with the metal oxide fine particles, which are inorganic components, and can contribute to improving the abrasion resistance, hardness, water resistance, etc. of the anti-fogging layer. However, if the content of the metal oxide (silica) component derived from the silane coupling agent is excessive, the anti-fogging properties of the anti-fogging layer are reduced, and in some cases the anti-fogging layer becomes cloudy. The metal oxide component derived from the silane coupling agent is added in a range of 0 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 2 parts by mass, relative to 100 parts by mass of the water-absorbing resin.
[0088] (Crosslinked structure) The anti-fogging layer may contain a crosslinked structure derived from a crosslinking agent, preferably at least one crosslinking agent selected from an organic boron compound, an organic titanium compound, and an organic zirconium compound. The introduction of the crosslinked structure improves the abrasion resistance, scratch resistance, and water resistance of the anti-fogging layer. From another perspective, the introduction of the crosslinked structure makes it easy to improve the durability of the anti-fogging layer without reducing its anti-fogging performance.
[0089] When a crosslinked structure derived from a crosslinking agent is introduced into an anti-fogging layer whose metal oxide component is a silica component, the anti-fogging layer may contain, as a metal atom, silicon as well as a metal atom other than silicon, preferably boron, titanium or zirconium.
[0090] The crosslinking agent is not particularly limited in type as long as it can crosslink the water-absorbent resin used. Here, only examples of organic titanium compounds are given. The organic titanium compound is, for example, at least one selected from titanium alkoxides, titanium chelate compounds, and titanium acylates. The titanium alkoxide is, for example, titanium tetraisopropoxide, titanium tetra-n-butoxide, and titanium tetraoctoxide. The titanium chelate compounds are, for example, titanium acetylacetonate, titanium ethyl acetoacetate, titanium octylene glycol, titanium triethanolamine, and titanium lactate. The titanium lactate may be an ammonium salt (ammonium titanium lactate). The titanium acylate is, for example, titanium stearate. A preferred organic titanium compound is a titanium chelate compound, particularly titanium lactate.
[0091] When the water-absorbing resin is a polyvinyl acetal, the preferred crosslinking agent is an organotitanium compound, especially titanium lactate.
[0092] In addition, when a crosslinked structure is formed by the hydrolyzable metal compound such as silicon alkoxide, the adhesion between the anti-fogging layer 7 and the mirror body 1 is improved, and the anti-fogging layer 7 can exhibit a shatterproof function. The amount of silicon alkoxide added in the coating liquid for the anti-fogging layer used to form the anti-fogging layer is 1 part by mass or more, preferably 1.5 parts by mass or more, and 50 parts by mass or less, preferably 30 parts by mass or less, per 100 parts by mass of the water-absorbing resin made of polyvinyl acetal or polyepoxy resin. If the amount of hydrolyzable metal compound added is small, the adhesion between the mirror body 1 and the anti-fogging layer 7 decreases, and the anti-fogging layer 7 becomes easily peeled off from the mirror body 1. On the other hand, if the amount of hydrolyzable metal compound added is large, the anti-fogging layer 7 becomes hard, and therefore easily breaks when the mirror body 1 breaks. Therefore, the shatterproof function of the anti-fogging layer 7 decreases.
[0093] (Other optional ingredients) The anti-fogging layer may contain other additives. Examples of the additives include glycols such as glycerin and ethylene glycol, which have the function of improving the anti-fogging properties. The additives may be surfactants, leveling agents, ultraviolet absorbers, colorants, defoamers, preservatives, etc.
[0094] (base layer) The anti-fogging layer 7 can be laminated directly on the glass plate 2, or an underlayer can be formed on the glass plate 2, and the anti-fogging layer 7 can be laminated on the underlayer. By laminating the anti-fogging layer 7 on the glass plate 2 via the underlayer in this manner, the anti-fogging layer 7 can be made less likely to peel off. For the underlayer, a silane coupling agent or the like can be used, for example.
[0095] [Film thickness] The thickness of the organic-inorganic composite anti-fogging layer may be appropriately adjusted according to the required anti-fogging properties and other factors. The thickness of the organic-inorganic composite anti-fogging layer is preferably 2 to 12 μm, more preferably 2 to 15 μm, and even more preferably 3 to 10 μm. If the thickness of the anti-fogging layer 7 is 2 μm or more, a sufficient anti-fogging effect can be obtained. However, if the anti-fogging layer 7 is too thick, its edge portion becomes easily visible, which is not preferable. In response to this, for example, as shown in FIG. 6, the anti-fogging layer 7 can be extended so as to cover the second chamfered portion 14 from the edge portion of the first main surface 11. Alternatively, it can be extended so as to cover the entire or part of the peripheral surface 13. In this way, even if the anti-fogging layer 7 is thick, its edge portion can be made invisible. In addition, if the anti-fogging layer 7 is too thick, the reflected image may be distorted due to unevenness in the thickness. In addition, since the anti-fogging layer 7 is formed of a resin material as described above and has birefringence, if it is too thick, the image may become blurred.
[0096] It is also possible to provide both the peripheral protective layer and the anti-fogging layer. In this case, the order of forming the anti-fogging layer 7 is not particularly limited, but for example, when the peripheral protective layer 5 shown in FIG. 4 is formed, it is preferable to form the anti-fogging layer 7 thereafter. This is because, if the anti-fogging layer 7 is formed first, the acidic solution contained in the solution for the anti-fogging layer may come into contact with the interface of each member exposed from the peripheral surface 13 of the mirror body 1, so in order to prevent this, it is preferable to form the peripheral protective layer 7 first. In this case, the anti-fogging layer 7 may be laminated on a part of the peripheral protective layer 5. In addition, the peripheral surface 13 of the mirror body 1 may be completely covered by either the peripheral protective layer 5 or the anti-fogging layer 7, or a part of it may be exposed. For example, at least a part of the end face of the glass plate 2 may be exposed.
[0097] However, when the anti-fogging layer 7 is extended to the peripheral surface 13 as described above, the thickness of the anti-fogging layer 7 formed on the peripheral surface 13 due to surface tension becomes larger than the thickness of the anti-fogging layer 7 formed on the first main surface 11. In consideration of productivity and cost, it is conceivable to form a large mirror body, laminate the anti-fogging layer thereon, and then cut out mirrors of sizes according to the requirements of various products. However, since the specifications such as the anti-fogging performance required differ depending on the type of product, it is preferable to cut the mirror body to the required product size and then laminate the anti-fogging layer 7. This makes it possible to reduce unnecessary inventory and accommodate multi-product production.
[0098] [hardness] The hardness of the anti-fogging layer 7 is preferably, for example, H to 2H in terms of pencil hardness as defined by JIS K5600-5-4. This is because if the anti-fogging layer is too hard, sufficient anti-fogging performance cannot be obtained, whereas if it is too soft, durability is poor.
[0099] [Anti-fogging layer formation range] The anti-fogging layer 7 can be laminated over the entire glass plate 2 as described above, but for example, when a frame body is provided to support the mirror body 1, the anti-fogging layer 7 can be avoided from being formed in the area where the frame body is attached. This is because the anti-fogging layer is easily damaged by the attachment of the frame body. The portion where the frame body is provided can be, for example, an area about 5 mm inward from the periphery of the glass plate. Such an area can be formed, for example, by masking the periphery of the glass plate 2 when forming the anti-fogging layer 7.
[0100] The above-mentioned anti-fogging layer is merely an example, and other known anti-fogging layers can be used, for example, various anti-fogging layers such as those described in JP-A-2001-146585. By forming the above-mentioned anti-fogging layer, the time until condensation occurs in the anti-fogging performance test described below can be set to 30 seconds or more, preferably 60 seconds or more, and more preferably 100 seconds or more.
[0101] The anti-fogging performance test can be performed in an environment with a room temperature of 20 to 23°C and a humidity of 20 to 23%RH as follows. First, as shown in FIG. 7, a cylinder with an inner diameter of 80 mm and an axial length of 60 mm was prepared and placed above a water tank containing water at 35°C. At this time, the distance between the upper end of the cylinder and the water surface of the water tank was set to 100 mm. Next, the mirror on which the anti-fogging layer 7 was formed was stored at 20°C and 30%RH for 30 minutes or more, and then placed so as to close the upper opening of the cylinder. At this time, the anti-fogging layer 7 was oriented downward and faced the water. Then, the time until the anti-fogging layer 7 became foggy was measured.
[0102] <4. Protective film> The anti-fogging layer 7 can also be covered with a protective film. The protective film can be composed of a sheet-like substrate and an adhesive layer laminated on one side of the substrate. The adhesive layer can be attached to the anti-fogging layer to protect the anti-fogging layer 7. The protective film is removed when the mirror is used. The material forming the substrate is not particularly limited, and can be formed of a resin material such as polyethylene terephthalate, polyvinyl chloride, polyvinylidene chloride, polycarbonate, acrylic resin, etc.
[0103] The adhesive layer may be any adhesive layer capable of fixing the substrate to the anti-fogging layer 7 with an appropriate strength. Specifically, an adhesive layer such as a resin obtained by copolymerizing acrylic, rubber, and methacrylic monomers with acrylic monomers having tackiness at room temperature and setting the desired glass transition temperature can be used. As the acrylic monomer, methyl acrylate, ethyl acrylate, butyl acrylate, stearyl acrylate, 2-ethylhexyl acrylate, etc. can be applied, and as the methacrylic monomer, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, stearyl methacrylate, etc. can be applied. In addition, when applying by heat lamination, etc., an organic material that softens at the lamination temperature may be used. For example, in the case of a resin obtained by copolymerizing methacrylic and acrylic monomers, the glass transition temperature can be adjusted by changing the compounding ratio of each monomer.
[0104] The thickness of the protective film is not particularly limited, but may be, for example, 30 to 90 μm. If the protective film is too thin, it may not be able to sufficiently protect the anti-fog layer 7, and may damage the anti-fog layer 7. On the other hand, if the protective film is too thick, it may be difficult to attach the film to the anti-fog layer.
[0105] The bending strength of the protective film is not particularly limited, but may be, for example, 96 to 131 MPa. If the bending strength of the protective film is low, the protective film may adhere to the edge of the anti-fog layer 7 and may be difficult to peel off. On the other hand, if the bending strength of the protective film is high, it may be difficult to attach the protective film to the anti-fog layer 7.
[0106] The protective film can cover the anti-fog layer 7 in various ways. For example, the protective film can be formed to have the same area as the anti-fog layer 7 to cover the entire anti-fog layer 7, or as shown in FIG. 8, the protective film 9 can be formed to protrude outward from the peripheral surface 13. In this way, the protruding portion can be grasped and the protective film 9 can be easily peeled off. In this case, the protruding portion may be bent so as to fit along the peripheral surface. Also, in order to reduce the protruding portion, only the portion corresponding to the second chamfered portion 14 can be made to protrude.
[0107] The anti-fogging layer 7 may be covered with one protective film, or may be covered with a plurality of protective films. That is, the protective film may be divided.
[0108] <5. Shatterproof layer> To prevent fragments from scattering when the mirror breaks, a shatterproof layer can be laminated on the protective layer 4. The shatterproof layer can be made of a resin material such as polyester, polyethylene terephthalate, polycarbonate, etc., and can be fixed to the protective layer 4 with an adhesive.
[0109] <6. Features> The mirror described above has the following advantages. (1) The first chamfered portion 132 formed on the mirror body 1 has the advantage that the mirror body 1 is less likely to chip when dropped. The second chamfered portion 14 can also provide a similar effect. (2) By forming the anti-fogging layer 7, the glass plate 2 of the mirror body 1 can be prevented from fogging up. (3) By forming the anti-fogging layer 7 on the first main surface 11 of the mirror body 1, impacts from the first main surface 11 side can be absorbed by the anti-fogging layer 7. As a result, even if the glass plate 2 itself is broken, glass fragments can be prevented from scattering. (4) As described above, the anti-fogging layer 7 can be made of various materials. For example, when the anti-fogging layer 7 is made of a material mainly composed of a water-absorbent resin, the anti-fogging layer 7 has the ability to absorb water and expand and contract, and can absorb impact. As a result, the impact can be mitigated and damage to the glass plate 2 can be suppressed. In addition, since the absorbent resin can expand and contract and is firmly bonded to the glass plate 2, even if the glass plate 2 is broken, scattering of glass fragments can be suppressed.
[0110] <7. Variations> Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the spirit of the present invention. The following modified examples can be appropriately combined.
[0111] In the above embodiment, an example in which a metal layer and a protective layer are laminated in this order on a glass plate has been described, but a semi-transmissive reflective film can be laminated instead. The semi-transmissive reflective film is a film that functions as a so-called half mirror. As an example, the semi-transmissive reflective film has a first layer laminated on a glass plate and a second layer laminated on the first layer. However, additional layers such as a third layer and a fourth layer can be provided as necessary. When a metal reflective layer made of a metal or a semi-metal is used as a layer constituting the semi-transmissive reflective film, one or more units consisting of two layers in which a low refractive index layer or a high refractive index layer is laminated directly on the metal reflective layer, or one or more units in which a low refractive index layer and a high refractive index layer are laminated in this order on the metal reflective layer can be laminated. When a metal reflective layer is not used, one or more units in which a low refractive index layer and a high refractive index layer are laminated in this order on the high refractive index layer can be laminated. The refractive index of the high refractive index layer is preferably 1.6 or more, and more preferably 1.8 or more. The refractive index of the low refractive index layer is lower than this, and is preferably, for example, 1.6 or less, and more preferably 1.5 or less. Note that the high refractive index layer and the low refractive index layer can also be formed by laminating one or more materials as long as the refractive index conditions are satisfied.
[0112] Next, the material of each layer of the semi-transmissive reflective film will be described. Each layer constituting the semi-transmissive reflective film can be formed by a layer made of a metal or a semi-metal and a layer made of an inorganic metal oxide (inorganic oxide layer), and is appropriately selected from, for example, silicon (Si), germanium (Ge), SUS or another suitable metal or semi-metal, silicon dioxide (SiO2), tin oxide (SnO2), titanium dioxide (TiO2), or another suitable inorganic metal oxide so as to satisfy the above-mentioned range of refractive index. For example, the refractive indexes of silicon, silicon dioxide, tin oxide, titanium dioxide, SUS, Ag, Al, Cr, Mo, and Ti are about 4.4, about 1.4, about 1.8, about 2.2, about 2.4, about 0.14, about 1.4, about 2.4, about 3.6, and about 2.7, respectively. The layer structure of the semi-transmissive reflective film is not particularly limited, but can be, for example, as follows. In addition, in order to adjust the electrical resistance of each layer, an additive can be appropriately doped. Instead of Si in the first layer in Examples 2 and 3, Ag, Al, Cr, Ti, or Mo can be used. [Table 1]
[0113] In addition, in Examples 1 and 3, SiO2 can be provided as a base layer between the first layer and the glass plate 2. In addition, the use of SUS can improve the visible light absorptance. When the visible light absorptance is improved, the total value of the visible light reflectance and the visible light transmittance is reduced, making it easier to adjust the visible light reflectance and the visible light transmittance.
[0114] When the semi-transmissive reflective film is formed from inorganic metal oxide containing the above-mentioned metal or semi-metal, the color tone does not change significantly when the semi-transmissive reflective film is viewed from a wide angle, so the mirror of the present invention is suitable as an optical cover glass. However, since the metal reflective layer is easily scratched, it is preferable that it is not placed on the outermost surface of the mirror. In addition, by providing an inorganic metal oxide layer, the alkali resistance can be improved.
[0115] The thickness (physical thickness) of the semi-transmitting reflective film is preferably 3 to 300 nm, and more preferably 5 to 250 nm. If the thickness of the semi-transmitting reflective film is less than 10 nm, it is difficult to control the thickness, resulting in poor productivity. On the other hand, if the thickness exceeds 300 nm, the cost may increase, the surface unevenness may become significant, or the haze rate may increase, resulting in poor appearance. In addition, the thickness of each layer constituting the semi-transmitting reflective film can be appropriately adjusted so that the thickness of the semi-transmitting reflective film falls within the above-mentioned range, and is not particularly limited. For example, in the above Example 2, a semi-transmitting reflective film can be formed in which the first layer is 18 nm, the second layer is 85 nm, and the third layer is 65 nm. In the above Example 4, the thickness of the silicon can be about 18 nm, and the thickness of the silicon dioxide can be about 30 nm. In addition, the thickness of the titanium dioxide in Examples 1 and 3 can be about 6 nm, and the thickness of the SUS in Example 5 can be about 8 nm.
[0116] In Example 2, in order to increase the reflection at the first layer, a low refractive index material can be laminated in the second layer and a high refractive index material can be laminated in the third layer. For example, as described above, if the first layer is 18 nm, the second layer is 85 nm, and the third layer is 65 nm, and the optical film thickness of the semi-transmissive reflective film is set to 135 nm±20 nm, the optical film thickness becomes λ / 4 for the wavelength λ of the incident light (center wavelength: 550 nm), and the reflection at the interface between the first layer and the second layer can be strengthened. As long as the film thickness and refractive index of each layer can be adjusted in this manner, materials other than those shown in Example 2 may be used.
[0117] The visible light transmittance of the mirror provided with the semi-transmissive reflective film is preferably 20% to 70%, more preferably 35% to 60%, and particularly preferably 35% to 50%. On the other hand, since the visible light reflectance of the mirror is in a trade-off relationship with the visible light transmittance, it is preferably 30% to 80%, more preferably 40% to 65%, and particularly preferably 50% to 65%.
[0118] The visible light transmittance and visible light reflectance of such a mirror can be adjusted by changing the material and film thickness of the semi-transmissive reflective film, and the material and thickness of the glass plate 2.
[0119] Next, a method for forming the semi-transmissive reflective film will be described. The method for forming the semi-transmissive reflective film is not particularly limited, but may be, for example, a so-called physical vapor deposition method such as a sputtering method or a vacuum deposition method, a spray method, or a chemical vapor deposition method (CVD method). In particular, when a CVD method is used, it is preferable to use an online CVD method. The online CVD method is a chemical vapor deposition method in which a material for a semi-transmissive reflective film is supplied from a coater onto the top surface of a glass ribbon that is on a molten tin bath and has a temperature of 615°C or higher, and a semi-transmissive reflective film is formed by a thermal decomposition oxidation reaction in a float glass manufacturing process.
[0120] To form each layer of the semi-transmissive reflective film, one material can be supplied from one coater, but if the layer is thick, one layer can be formed using two or more coaters. For example, in the above Example 4, when the silicon film thickness is 18 nm and the silicon dioxide film thickness is 30 nm, the semi-transmissive reflective film can be formed by preparing first to third coaters, supplying silicon from the first coater, and supplying silicon dioxide from the second and third coaters.
[0121] The above-mentioned SUS film is formed by sputtering, not CVD. In addition, sputtering is preferably used to form a thin film of a material. EXAMPLES
[0122] Examples of the present invention will be described below. However, the present invention is not limited to the following examples. In the following, the performance of the anti-fogging film will be evaluated.
[0123] (1) Preparation of the mirror for the embodiment A mirror as a test sample was prepared as follows.
[0124] (i) Mirror body A mirror body was prepared in which the above-mentioned semi-transmissive reflective film was laminated on the second main surface of a glass plate (soda-lime silicate glass, thickness 3.1 mm, size 100×100 mm).
[0125] (ii) Anti-fog layer A solution containing 62.5 mass% polyvinyl acetal resin (Sekisui Chemical Co., Ltd. "S-LEC KX-5", solid content 8 mass%, degree of acetalization 9 mol%, containing an acetal structure derived from benzaldehyde), 1.04 mass% tetraethoxysilane (TEOS, Shin-Etsu Chemical Co., Ltd. "KBE-04"), and titanium lactate (Matsumoto Fine Chemical Co., Ltd. "Orgatics TC-310"; Ti(OH)2[OCH(CH3)COO A coating solution for forming an anti-fog layer was prepared by placing 1.21 mass% of a solution containing 44 mass% of [H2]2 and using a mixed solvent of 2-propanol and water, 17.79 mass% of an alcohol solvent ("Solmix AP-7" manufactured by Nippon Alcohol Industry Co., Ltd.), 17.44 mass% of purified water, 0.01 mass% of nitric acid as an acid catalyst, and 0.01 mass% of a leveling agent ("KP-341" manufactured by Shin-Etsu Chemical Co., Ltd.) in a glass container and stirring at room temperature (25°C) for 3 hours.
[0126] Next, the coating liquid was applied to the first main surface of the mirror body by flow coating at room temperature of 20°C and relative humidity of 30%. After drying for 10 minutes in the same environment, a (preliminary) heat treatment at 120°C was performed. Thereafter, a high-temperature and high-humidity treatment was performed using the above-mentioned atmosphere and time, and an additional heat treatment was performed using the above-mentioned atmosphere and time to produce a mirror according to the embodiment. The anti-fogging layer had a thickness of 3.9 μm.
[0127] The mirror produced as described above was subjected to the following evaluations. First, the peeling of the anti-fogging layer was evaluated using the cross-cut method specified in JIS K5600-5-1. As a result, it was rated as Class 0 (the edges of the cuts were completely smooth and there was no peeling at any of the lattice meshes). Therefore, it was found that the anti-fogging layer according to the embodiment exhibited high adhesion to the mirror body. It is considered that even a Class 1 rating is acceptable for practical use.
[0128] Next, the shatterproof function was evaluated. First, a straight cut was formed on the second main surface of the mirror body 1 with a glass cutter. Note that a wheel cutter or a diamond cutter can be used instead of the glass cutter. Next, a round bar with a diameter twice the thickness of the glass plate was placed on the horizontal surface. Next, the anti-fogging layer was placed facing downwards on the round bar, and the mirror was placed on the round bar. At this time, the round bar was brought into contact with the anti-fogging layer so as to correspond to the cut (to extend along the cut). After that, both sides of the cut on the second main surface of the mirror body were simultaneously pressed toward the horizontal surface to split the mirror body. At this time, when it was confirmed whether the anti-fogging layer was cut or not, the anti-fogging layer was not cut. Therefore, it was found that the anti-fogging layer does not break even if the mirror body is broken, and therefore it is possible to prevent fragments of the broken mirror body from scattering. [Explanation of symbols]
[0129] 1 Mirror body 11 First main surface 12 Second main surface 13 Peripheral surface 132 First chamfer 14 Second chamfer 2 Glass plate 3 metal layer 5 Protective layer 7 Anti-fog layer
Claims
1. A mirror body having a polygonal shape in a plan view, the mirror body having a first main surface on which an image is reflected, a second main surface opposite to the first main surface, and a peripheral surface connecting the first main surface and the second main surface; An anti-fogging layer; Equipped with The peripheral surface includes a plurality of first end surfaces and second end surfaces connecting adjacent first end surfaces, The second end surface constitutes a first chamfered portion formed on an outer edge of the mirror body in a plan view, a second chamfered portion is formed between the first main surface and the peripheral surface; A mirror, wherein the anti-fogging film is formed by a coating film covering at least a portion of the first main surface and the second chamfered portion.
2. The mirror of claim 1 , wherein the anti-fogging layer and the first main surface are chemically bonded to each other.
3. The mirror according to claim 1 or 2, further comprising an undercoat layer disposed between the anti-fogging layer and the first main surface.
4. The mirror according to claim 1 , wherein the anti-fogging layer is disposed so as to cover the peripheral surface.
5. 5. The mirror according to claim 4, wherein the anti-fog layer has a pencil hardness of H to 2H.
6. 6. The mirror according to claim 1, wherein the antifogging layer has a thickness of 2 to 12 μm.
7. 7. The mirror according to claim 1, wherein the anti-fogging layer is not disposed in a peripheral region of a predetermined width extending from the periphery of the first main surface toward the center.
8. 8. The mirror according to claim 1, wherein the entire first main surface is covered with the anti-fogging layer.
9. The anti-fogging layer is disposed so as to cover the peripheral surface, 9. The mirror according to claim 1, wherein a thickness of the anti-fogging layer disposed on the peripheral surface is greater than a thickness of the anti-fogging layer disposed on the first main surface.
10. 10. The mirror according to claim 1, wherein the anti-fogging layer has anti-fogging properties due to hydrophilicity.
11. The mirror according to claim 10, wherein the anti-fogging layer further has an anti-fogging property due to water absorption.
12. The mirror according to claim 10, wherein the anti-fogging layer is made of a material containing a water-absorbent resin as a main component.
13. The mirror according to claim 12, wherein the water-absorbing resin contains at least one of an epoxy resin and a polyvinyl acetal resin.
14. 14. The mirror according to claim 1, wherein the anti-fogging layer has a shatterproof function.
15. The mirror according to claim 14 , wherein the anti-fogging layer has a cross-linked structure formed by a hydrolyzable metal compound.
16. 16. The mirror of claim 15, wherein the hydrolyzable metal compound comprises a silicon alkoxide.
17. 17. The mirror according to claim 14, wherein the adhesion of the anti-fogging layer to the mirror body is classified as 0 or 1 in a cross-cut test specified in JIS K5600-5-6.
18. A mirror as described in any one of claims 14 to 17, in which a linear cut is formed on the second main surface of the mirror body with a cutter, a round rod arranged on a horizontal plane is brought into contact with the anti-fogging layer facing downward to correspond to the cut, and both sides of the cut are pressed, so that when the mirror body is split, the anti-fogging layer is not cut.
19. 19. The mirror of claim 1, further comprising a protective film covering the anti-fog layer.
20. The protective film has a sheet-like substrate and an adhesive layer disposed on one surface of the substrate, The adhesive layer adheres the substrate to the anti-fogging layer, The mirror according to claim 19 , wherein the peripheral edge of the base material has an area where the adhesive layer is not disposed.
21. The anti-fogging layer is disposed so as to cover the peripheral surface, 21. The mirror of claim 20, wherein the protective film is not adhered to at least a portion of the anti-fog layer covering the peripheral surface.
22. 22. The mirror according to claim 19, wherein the protective film is formed so as to protrude from the mirror body at a location where the first chamfered portion is formed.
23. 23. The mirror according to any one of claims 19 to 22, wherein the protective film has a bending strength of 96 to 131 MPa.
24. The mirror according to any one of claims 19 to 23, wherein the protective film has a thickness of 30 to 90 µm.
25. The mirror according to any one of claims 19 to 24, wherein the protective film is configured to cover the anti-fogging layer in a state in which the protective film is divided into a plurality of pieces.
26. The mirror body includes: A metal layer or a semi-metal layer laminated on one surface of the glass plate; a resin protective layer laminated on the metal layer or semi-metal layer; 26. The mirror according to claim 1, further comprising an inorganic oxide layer made of an inorganic oxide laminated between the metal layer or semi-metal layer and the protective layer.
27. 27. The mirror of claim 26, wherein the semi-metallic layer is based on Si or Ge.
28. The mirror body includes: A glass plate and A metal layer laminated on one surface of the glass plate; 26. The mirror according to claim 1, further comprising a resin protective layer laminated on the metal layer.
29. the other surface of the glass plate constitutes the first main surface; 30. The mirror of claim 28, further comprising an anti-fog layer disposed over the first major surface.
30. In the peripheral surface, 30. The mirror of claim 28 or 29, further comprising a peripheral protective layer disposed over a first interface between the glass plate and the metal layer and a second interface between the metal layer and the protective layer.
31. the other surface of the glass plate constitutes the first main surface; An anti-fogging layer is disposed so as to cover the first main surface, In the peripheral surface, a peripheral protective layer disposed to cover a first interface between the glass sheet and the metal layer and a second interface between the metal layer and the protective layer; 29. The mirror of claim 28, wherein a portion of the anti-fog layer covers the peripheral protective layer.
32. 32. The mirror according to claim 30 or 31, wherein the peripheral protective layer is formed of an ultraviolet curable resin.
33. 33. The mirror according to claim 30, wherein an end face of the glass plate exposed to the outside at the peripheral surface has an area that is not covered with the peripheral protective layer.
34. The mirror further includes a shatterproof film for preventing fragments from scattering when the mirror body is broken.
34. A mirror as claimed in any one of claims 28 to 33, wherein the shatterproof film is disposed over the protective layer.
35. 35. A mirror according to any one of claims 28 to 34, wherein the protective layer carries a plurality of types of information.
36. 36. A mirror according to claim 1, wherein the anti-fogging layer takes 30 seconds or longer to form condensation.
Citation Information
Patent Citations
JP1961026752Y1
JP1980028136U
Antifogging substrate and forming method therefor
JP2001146585A
Manufacturing method for defogging mirror and mirror material sheet
JP2002078587A
Vehicle with Anti-fogging glass and set of vehicle window glass
JP2008114760A
Cited By
Semiconductor device
CN122766035A